Efficacy and Safety of Veverimer in the Treatment of Metabolic Acidosis Caused by Chronic Kidney Disease: A Meta-analysis - Liu, Wenlin; Li, Lili; Zhang, Xuemei; Dong, Haonan; Lu, Miaomiao (Frontiers in Pharmacology, 2021)
Metabolic acidosis is a common complication of chronic kidney disease (CKD). Veverimer is an orally administrated, free amine polymer with high capacity and binding selectivity to hydrochloric acid from the gastrointestinal tract. This study pooled the current evidence of the efficacy and safety of veverimer for the treatment of metabolic acidosis associated with CKD. We conducted a systematic literature search on PubMed, Embase, and Cochrane Central for relevant randomized controlled trials (RCTs) in June 2020. In this study, three RCTs with 548 patients were included in our analysis. The analysis revealed that veverimer was associated with increased bicarbonate level of patients (weight mean difference [WMD] 3.08, 95% confidence interval [CI] [2.40, 3.77], P<0.001) and improved physical function compared with placebo measured by Kidney Disease and Quality of Life Short Form (SF)36, question 3 (physical functioning domain) (KDQoL-PFD) score (WMD 5.25, 95% CI [1.58, 8.92], P=0.005). For safety outcomes, both groups exhibited similar risks for developing headache, diarrhea, flatulence, and hyperkalemia. In conclusion, current clinical evidence indicates that veverimer is efficacious and safe against metabolic acidosis related to CKD compared with placebo. Further research comparing long-term veverimer use with traditional alkali therapy is needed.